Dampak Pedagang Kaki Lima dan Warung Kecil Pasca Relokasi di Sentra Wisata Kuliner Ketintang - Febriana Firsta Damayanti; Pambudi Handoyo (JIP ( Jurnal Industri dan Perkotaan ), 2023)
Relocation is an attempt to move an object from one place to another that is considered better. Relocation is not just a change of place in terms of geographical space, but also involves various aspects such as economic, social, political and cultural. The socio-economic impact of the relocation of street vendors (PKL) and small stalls can be seen from the positive and negative sides. If done properly by considering the interests of all parties, relocation can have a positive social impact. The impact felt by street vendors and small stalls will be seen when a relocation that is realized can show changes socially and economically so that it can be assessed whether the relocation carried out is considered successful or failed. The purpose of writing this article is to find out and examine how the problems regarding the impact of street vendors and small stalls after relocation in the Ketintang culinary tourism center. This research is a qualitative research with a framing analysis approach related to social interaction theory and also conflict theory accompanied by interview techniques and direct observation in Ketintang. The results of this study indicate that relocation to the Ketintang Culinary Tourism Center can help the economy and social life of traders to improve so that traders feel a very profitable positive impact. Relocation that is carried out well as a whole can have a good social impact for traders, whereas irregular relocation can have a negative impact on the sustainability of the street vendors and small shop businesses.Keywords: Street vendor, Relocation, Small stalls